2008
DOI: 10.1108/02651330810887468
|View full text |Cite
|
Sign up to set email alerts
|

The effects of country of origin and corporate reputation on initial trust

Abstract: Purpose -The purpose of this paper is to investigate the simultaneous effects of country of origin (COO) and corporate reputation on initial trust in a transition economy, and to compare these effects across two service industries. The model broadens COO research by incorporating initial trust as a key driver of success in the context of services internationalization. Design/methodology/approach -Poland is the transition economy studied. A total of 184 respondents evaluated different service combinations (high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(25 citation statements)
references
References 87 publications
2
20
0
3
Order By: Relevance
“…Moreover, reputation of firms from an emerging market has an indirect effect on purchase decision through trust. This empirical observation coincides with the findings of Michaelis et al (2008), who hold that consumers facing an uncertain purchase situation (the case of value products from emerging countries) primarily draw on indicators that signal foreign product quality (such as the reputation of the COO firms) until when they start to trust a foreign firm. In line with the above argument, a foreign firm's reputation is the key deciding factor in consumer purchase decision in our study.…”
Section: Wwwccsenetorg/ijbmsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, reputation of firms from an emerging market has an indirect effect on purchase decision through trust. This empirical observation coincides with the findings of Michaelis et al (2008), who hold that consumers facing an uncertain purchase situation (the case of value products from emerging countries) primarily draw on indicators that signal foreign product quality (such as the reputation of the COO firms) until when they start to trust a foreign firm. In line with the above argument, a foreign firm's reputation is the key deciding factor in consumer purchase decision in our study.…”
Section: Wwwccsenetorg/ijbmsupporting
confidence: 62%
“…In terms of the theory of signals, reputation is more useful as a generator of trust when firms and their products are not well known, as happens with foreign firms and products (Nijssen, Singh, Sirdeshmukh & Holzmuelle, 2003). Under such circumstances, reputation of firms from a particular country becomes an evaluation criterion for available offer and a cornerstone in the construction of a trust-based relationship (Michaelis, Woisetschläger, Backhaus & Ahlert, 2008;Nijssen & Herk, 2009). Thus, the first hypothesis proposes that:…”
Section: Components Of Coo Effect and Their Consequencesmentioning
confidence: 99%
“…Globalization gives the chance to companies to distribute their products all over the world, and presents the opportunity for people to choose between different types of product; consequently, country of origin is a significant subject when examining consumer purchase behaviour according to foreign products. In addition, it is also a label for brands, which guides the consumers to know the firm and the country of origin (Chen, Wu, & Chen, 2011;Michaelis, Woisetschläger, Backhaus, & Ahlert, 2008).…”
Section: Background Of Country Of Originmentioning
confidence: 99%
“…This also implicates medical tourism because the recent trend is for people to travel from developed countries to third--world countries for medical treatments because of cost consideration. However, the study conducted by Michaelis et al (2008) showed that a positive COO effect leads to a higher level of initial trust only in the case of a risky service.…”
Section: Relationships Between Coo and Psfmentioning
confidence: 99%
“…Most of the study in this area lies in the fields of cross-country marketing and culture studies. To sum up, considering services, the COO is an essential carrier of information for consumers (Ahmed, Johnson, Ling, Fang, Nui, 2002) which affects their assessment of purchase risk (Michaelis Woisetschläger, Backhaus, Ahlert, 2008) and purchase intentions (Harrison-Walker, 1995;Morrish, Lee, 2011). Moreover, it serves as a cue from which consumers make inferences about a product and product attributes, such as evaluation of quality or performance.…”
Section: Country Of Service Origin and Country-of-service-origin Effectmentioning
confidence: 99%